BUYING BEHAVIOUR OF MILLENNIAL TOWARDS ORGANIC PRODUCTS IN CHENNAI CITY - J. Aruna; C. Sankar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the buying behaviour of millennials towards organic products, exploring the factors that influence their purchasing decisions. A mixed-methods approach was employed, The results show that millennials prioritize health, environmental concerns, and sustainability when purchasing organic products. Key drivers of purchase intentions include Perceived health benefits, Environmental consciousness, Social influence, Product labelling and certification, Price sensitivity. The study also reveals significant differences in buying behaviour between millennial sub-groups, including variations based on age, income, and education level. The findings provide valuable insights for marketers and manufacturers of organic products, highlighting the importance of effective labelling, eco-friendly packaging, and digital marketing strategies to appeal to this demographic.